2018
DOI: 10.7567/jjap.57.08rc16
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption spectra of Cu2ZnSn(S,Se)4 thin-film solar cells by Fourier transform photocurrent spectroscopy

Abstract: We demonstrated the potential of Fourier transform photocurrent spectroscopy (FTPS) in investigating the optical absorption and quality of a Cu 2 ZnSn(S,Se) 4 (CZTSSe) absorber within the cell structure. We fabricated thin-film solar cell structures with a CZTSSe absorber, which was prepared by a nanoparticle coating technique and a postannealing process. The optical absorption spectra of CZTSSe absorbers prepared at different annealing temperatures were measured by FTPS. We successfully evaluated the optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It is interesting to note that the inclusion of a reduced effective band gap due to band gap fluctuations (that lead to sub-band-gap absorption) was found to be essential in drift-diffusion simulations (using wxAMPS, SCAPS, and Sentaurus) to reproduce the experimentally measured IV characteristics. Urbach tails in kesterites have been characterized using photothermal deflection spectroscopy and Fourier transform photocurrent spectroscopy. E U values of 53 meV and ∼30 meV were reported for CZTS and Se-rich kesterites, respectively. More importantly, it was shown that the presence of both band gap fluctuations and an Urbach tail is needed to fit the experimentally measured absorption coefficient (Figure ). These reports also showed an exponential tail in the absorption coefficient over 4 orders of magnitude spanning an energy range of ∼0.3–0.4 eV below the band gap, revealing the presence of deep sub-band states in kesterites (Figure ).…”
Section: Emerging Chalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that the inclusion of a reduced effective band gap due to band gap fluctuations (that lead to sub-band-gap absorption) was found to be essential in drift-diffusion simulations (using wxAMPS, SCAPS, and Sentaurus) to reproduce the experimentally measured IV characteristics. Urbach tails in kesterites have been characterized using photothermal deflection spectroscopy and Fourier transform photocurrent spectroscopy. E U values of 53 meV and ∼30 meV were reported for CZTS and Se-rich kesterites, respectively. More importantly, it was shown that the presence of both band gap fluctuations and an Urbach tail is needed to fit the experimentally measured absorption coefficient (Figure ). These reports also showed an exponential tail in the absorption coefficient over 4 orders of magnitude spanning an energy range of ∼0.3–0.4 eV below the band gap, revealing the presence of deep sub-band states in kesterites (Figure ).…”
Section: Emerging Chalcogenidesmentioning
confidence: 99%
“…(b) Experimentally measured IQE showing exponential absorption tails in CZTSSe absorbers annealed at various temperatures (band gaps of these absorbers range from 1.28 to 1.32 eV). Reproduced with permission from refs and . Copyright 2018 IOP Publishing and 2018 Elsevier.…”
Section: Emerging Chalcogenidesmentioning
confidence: 99%